Factors for Increasing Goat Productivity with Probiotic Supplements in Kalipuro and Pesanggaran, Banyuwangi - Hamid, Iwan Sahrial; Fikri, Faisal; Tito, Muhammad (Universitas Airlangga, 2023)
Goat farming is an economic sector asset to support food availability and security in Banyuwangi. The existence of livestock is mainly to be supported by the adequacy of feed in order to increase productivity. This study is to evaluate the factors that play a role in increasing livestock productivity by adding probiotics to feed. The method used is surveys and questionnaires to farmers to evaluate farmers' understanding of feed quality. The results of 45 farmers as respondents, reported factors of knowledge (p<0.000), age (p<0.000), and application of feed (p<0.000) which significantly affect livestock productivity. It can be concluded that the level of knowledge, age, and application of feed are crucial factors for farmers to increase livestock productivity.